1980
DOI: 10.1080/03014468000004581
|View full text |Cite
|
Sign up to set email alerts
|

Growth velocity in children in rural Khartoum, Sudan

Abstract: The results of a mixed cross-sectional and longitudinal anthropometric survey of Sudanese children up to the age of sixteen years are reported. Weight velocity, height velocity, mid arm circumference velocity, and mid arm muscle circumference velocity, and the age at which 50% of females have reached menarche have been calculated. Growth velocities are lower than for English children and the puberty growth spurts occurs about one year later in Sudanese than in English children

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…We found that APHV was 8 months later in black males than in white males, while it was 3 months earlier in black females than in white females. A similar pattern has been described in Sudanese adolescents, with a delay of 1 year in APHV being observed in Sudanese males compared to their British peers living in the United Kingdom, but not in females (Sukkar, Kemm, Ballal, & Ahmed, 1980). Additionally, the delay in APHV in our cohort is corroborated by the finding in the same cohort of a 6‐month delay in skeletal maturity in black males compared to their white peers but not in females during puberty.…”
Section: Discussionsupporting
confidence: 74%
“…We found that APHV was 8 months later in black males than in white males, while it was 3 months earlier in black females than in white females. A similar pattern has been described in Sudanese adolescents, with a delay of 1 year in APHV being observed in Sudanese males compared to their British peers living in the United Kingdom, but not in females (Sukkar, Kemm, Ballal, & Ahmed, 1980). Additionally, the delay in APHV in our cohort is corroborated by the finding in the same cohort of a 6‐month delay in skeletal maturity in black males compared to their white peers but not in females during puberty.…”
Section: Discussionsupporting
confidence: 74%
“…There are just a handful of longitudinal studies in the literature with data on velocity of growth rate in school-age children. When comparing the growth rate in normal Sudanese children to the Tanner standard, Sukkar et al (1980) found mean values for velocity, both in weight gain and in height, below the standard; the typical pubertal period of growth spurt happened a year later. When comparing these normal Sudanese children to the present N and S groups, values for velocity of growth rate were shown to be lower than the Sudanese children at baseline study, but similar at the end of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Following the recommendations of the WHO Working Group (WHO, 1986), there has been an upsurge of interest in the use of velocity measurements during infancy (Healy et al, 1988a;Piwoz et al, 1992). Several studies have examined growth velocity standards for children and teenagers in America (Buschang et al, 1986;Pomerance and Krall, 1985;Tanner and Davies, 1985), Australia (Williams et al, 1990), Europe (Holmquist, 1991;Kemper et al, 1985;Michaelsen et al, 1994;Tanner and Cameron, 1980;Voss et al, 1991), Middle East (Bhalla et al, 1986;Liu et al, 1998), and Africa (Healy et al, 1988a;Sukkar et al, 1980). Height and weight velocities predominate in these studies.…”
mentioning
confidence: 99%